The Influence of Digital Recruitment Transformation, Work Experience, and Education Level on Generation Z's Interest in Seeking Employment Abroad: A Study on Generation Z in Jabodetabek and Bandung - Shàn Noël Yearry; Dyah Ayu Puri Palupi (STEBIS Bina Mandiri, 2026)
This study is about the influence of digital recruitment transformation (X1), work experience (X2), and education level (X3) on Generation Z's interest in seeking employment abroad (Y) in the Jabodetabek and Bandung areas of Indonesia. Digital technology has changed the way job seekers look for work opportunities rapidly, and this shift is directly visible among Generation Z, who grew up with the internet and digital platforms. At the same time, issues such as mismatched qualifications, low wages, and toxic work environments in Indonesia have pushed many young workers to consider working in another country. Using a quantitative approach with questionnaire data from 100 respondents, this study applies multiple linear regression analysis through SPSS v29. The results show that all three variables — digital recruitment transformation, work experience, and education level — have a positive and significant effect on Generation Z's intention to actively pursue employment abroad, both partially and simultaneously. Work experience has the strongest influence, followed by education level and digital recruitment transformation. The adjusted R-square value of 0.451 indicates that the three variables explain 45.1% of the variation in the dependent variable. This study suggests that companies, educational institutions, and policymakers must respond to the needs and expectations of Generation Z to prevent further talent drain from Indonesia.